2021
DOI: 10.1002/rcm.9035
|View full text |Cite
|
Sign up to set email alerts
|

SpheriCal®‐ESI: A dendrimer‐based nine‐point calibration solution ranging from m/z 273 to 1716 for electrospray ionization mass spectrometry peptide analysis

Abstract: Rationale A calibration solution for mass spectrometry needs to cover the range of interest with intense and sufficiently narrowly spaced peaks. Limited options fulfilling this may lead to compromises between performance and ease of use. SpheriCal®‐ESI was designed to combine high calibration performance for electrospray ionization (ESI) mass spectrometric analysis of peptides in positive mode with quick and easy use. Methods The developed calibration solution was tested using three mass spectrometers: two ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Protonated, deprotonated, and Na + ‐adducted analytes showed no obvious mass shifts relative to the calibration solution used (see supporting information ‐ Supplementary mass shifts Figures 5–20), except in the extended mass range where two of the high‐mass dendrimers showed error toward lower m/z relative to protonated ESI tuning mix (Figure 2). In line with these results, previous studies on lower mass Na + ‐adducted dendrimers of SpheriCal®‐ESI showed no mass shifts relative to peptides, and no peak distortion, on the amaZon 16 . The Cs + ‐adducted high‐mass dendrimers showed mass shifts compared to the Na + ‐adducted dendrimers, but not as severe as the shifts of some of the cluster ions (Figure 2).…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…Protonated, deprotonated, and Na + ‐adducted analytes showed no obvious mass shifts relative to the calibration solution used (see supporting information ‐ Supplementary mass shifts Figures 5–20), except in the extended mass range where two of the high‐mass dendrimers showed error toward lower m/z relative to protonated ESI tuning mix (Figure 2). In line with these results, previous studies on lower mass Na + ‐adducted dendrimers of SpheriCal®‐ESI showed no mass shifts relative to peptides, and no peak distortion, on the amaZon 16 . The Cs + ‐adducted high‐mass dendrimers showed mass shifts compared to the Na + ‐adducted dendrimers, but not as severe as the shifts of some of the cluster ions (Figure 2).…”
Section: Resultssupporting
confidence: 86%
“…In line with these results, previous studies on lower mass Na + ‐adducted dendrimers of SpheriCal®‐ESI showed no mass shifts relative to peptides, and no peak distortion, on the amaZon. 16 The Cs + ‐adducted high‐mass dendrimers showed mass shifts compared to the Na + ‐adducted dendrimers, but not as severe as the shifts of some of the cluster ions (Figure 2 ). As it has been shown that, for example, protonated and Na + ‐adducted analytes had different stabilities, 4 , 6 , 8 we assume that the difference found here between Na + adducts and Cs + adducts has a similar origin.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations